Perancangan Sistem Absensi Online Bagi Karyawan/ Mahasiswa Praktik Kerja Lapangan Pada Divisi Costumer Care Menggunakan Aplikasi Google Form Tahun Akademik 2022/2023 - Muh Syafruddin Akmal; Nurul Fadhilah (Sakura Digital Nusantara, 2023)
Research in this community service activity was carried out at the office of a State-Owned Enterprise (BUMN), PT. Telkom Indonesia Makassar City Jl. City Hall, No. 5. The activity aims to make it easier for street vendors to carry out attendance activities when they arrive at the office and also when they are going back to their respective homes and to help when carrying out daily activities and logbook reports. This activity is also useful for street vendor employees to be able to make it easier when going to come and go home and is useful to make it easier when making a final report on street vendor activities. This research uses the research and development method of R&D (Research and Development). This research has research results in the form of a product in the form of an online attendance system on the Google form application which can be used by street vendors when they are going to take attendance, return attendance and also make daily activity reports/logbooks